(untitled) (Neo Science Peer Reviewed Journal, 2023)
The article analyzes the efficiency of small business and private entrepreneurship, its socio-economic efficiency, the development of small business and the increase in the standard of living of the population, as well as ensuring economic, social and political stability in the country and its role in it.